Gangues and Clays Minerals as Rate-Limiting Factors in Copper Heap Leaching: A Review - Toro, Norman; Ghorbani, Yousef; Turan, Mehmet Deniz; Robles, Pedro; Galvez, Edelmira (Mdpi, 2021)
Heap leaching is a firm extractive metallurgical technology facilitating the economical processing of different kinds of low-grade ores that are otherwise not exploited. Nevertheless, regardless of much development since it was first used, the process advantages are restricted by low recoveries and long extraction times. It is becoming progressively clear that the selection of heap leaching as an appropriate technology to process a specific mineral resource that is both environmentally sound and economically feasible very much relies on having an ample understanding of the essential underlying mechanisms of the processes and how they interrelate with the specific mineralogy of the ore body under concern. This paper provides a critical overview of the role of gangues and clays minerals as rate-limiting factors in copper heap leaching operations. We aim to assess and deliver detailed descriptions and discussions on the relations between different gangues and clays minerals and their impacts on the operational parameters and chemical dynamics in the copper heap leaching processes.
Keywords: hydrometallurgy; leaching; gangues; clays minerals; heap leaching; agglomeration